Spectrophotometric Determination of Famciclovir and Racecodotril - Gowri Sankar, D.; Pawar, A.K.M.; Kalyan Sumanth, S.; Madhavi Latha, P.V. (Asian Journal of Chemistry, 2016)
Simple and sensitive UV spectrophotometric methods have been developed for the determination of famciclovir and racecodotril in pure and pharmaceutical dosage forms. These methods obey Beer's law in the concentration range of 10–60 and 20–100 μg/mL exhibiting absorption maximum at 305 and 211 nm respectively. These methods are extended to pharmaceutical preparations and there is no interference from any common pharmaceutical additives and diluents. The methods have been statistically evaluated and are found to be precise and accurate.